A Positive theory of monetary policy and robust control - Juha Kilponen (Bank of Finland, 2003)
This paper applies the robust control approach to a simple positive theory of monetary policy, when the central bank's model of the economy is subject to misspecifications.It is shown that a central bank should react more aggressively to supply shocks when the model misspecifications grow larger.Moreover, the model misspecifications aggravate the inflation bias and a trade-off between output stabilisation and inflation worsens when the uncertainty surrounding the central bank's model increases.This implies that the larger the model misspecifications are, the more inflation-averse the central bank should be.
URN:NBN:fi:bof-20140807538
Keywords: E58; 330; risk-sensitivity; robust control theory; monetary policy; Brainard conservatism; model uncertainty